Toothbrushing Behavior and Handgrip Strength among Children with Intellectual Disabilities: a Cross-Sectional Study - Muhammad Fiqih Sabilillah; Hari Kusnanto; Lisdrianto Hanindriyo; Sri Kuswandari (INKLUSI, 2025)
Children with intellectual disabilities have cognitive limitations, fine motor impairments and low conceptual understanding, which hinder their ability to perform self-care activities independently, including brushing their teeth. Limited fine motor skills can affect their ability to grip and control a toothbrush, making hand grip strength a relevant variable in efforts to enhance the independence of children with intellectual disabilities in brushing their teeth. The aim of this study is to analyze the relationship between toothbrushing behavior and hand grip strength in children with intellectual disabilities. This study employs an observational analytic design with a cross-sectional approach. The sample selection was conducted using purposive sampling, resulting in 38 respondents. Toothbrushing behavior has a significant relationship with hand grip strength in children with intellectual disabilities. Variables such as frequency, duration and brushing time (morning and night) consistently influence grip type, strength control, independence, grip duration, stability and grip precision. Repeated toothbrushing with a specific pattern can improve fine motor strength and support children's independence and quality of life. Anak disabilitas intelektual memiliki keterbatasan kognitif, ketidakmampuan motorik halus dan rendahnya pemahaman konseptual sehingga menghambat melaksanakan kegiatan kebersihan diri secara mandiri, termasuk menyikat gigi. Kemampuan motorik halus yang terbatas, dapat mempengaruhi kemampuan anak menggenggam dan mengontrol sikat gigi maka kekuatan genggaman tangan menjadi variabel yang relevan dalam upaya meningkatkan kemandirian anak disabilitas intelektual menyikat gigi. Tujuan penelitian ini adalah untuk menganalisis hubungan perilaku menyikat gigi dengan kekuatan genggaman tangan pada anak disabilitas intelektual. Desain penelitian ini menggunakan pendekatan observasional analitik dengan metode cross-sectional. Pemilihan sampel dilakukan dengan metode purposive sampling dan didapatkan 38 responden. Perilaku menyikat gigi memiliki hubungan signifikan dengan kekuatan genggaman tangan anak disabilitas intelektual. Variabel frekuensi, durasi dan waktu menyikat gigi (pagi dan malam) secara konsisten mempengaruhi jenis genggaman, kontrol kekuatan, kemampuan mandiri, durasi genggaman, stabilitas dan presisi genggaman. Pengulangan menyikat gigi dengan pola tertentu akan meningkatkan kekuatan motorik halus anak dan mendukung kemandirian dan kualitas hidup.